2011
DOI: 10.5977/jkasne.2011.17.3.424
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Communication Education in the Undergraduate Nursing Curriculum of Korea

Abstract: 의사소통 교과목 학습내용연구대상 의사소통 교육방법 및 평가방법Purpose: This study was done to investigate the current conditions with communication-related education in the nursing undergraduate curriculum, and to develop effective strategies for communication education. Methods: We collected 48 syllabi of communication-related courses from the nursing college or nursing department of a university and analyzed the syllabi using the content analysis method. Results: First, in the knowledge domain, 'Theories of communication', 'Characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 9 publications
(2 reference statements)
0
5
0
2
Order By: Relevance
“…However, according to a study on the current status of communication education [4], more than 90% of domestic nursing colleges were found to implement lecturebased teaching methods, and 95.8% of colleges were evaluating students on the basis of test performance and attendance. The traditional lecture-centered education method for communication has become an underlying cause of the difficulty that nursing students experience when interacting with various subjects and other medical staffs [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, according to a study on the current status of communication education [4], more than 90% of domestic nursing colleges were found to implement lecturebased teaching methods, and 95.8% of colleges were evaluating students on the basis of test performance and attendance. The traditional lecture-centered education method for communication has become an underlying cause of the difficulty that nursing students experience when interacting with various subjects and other medical staffs [5].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the omission of patient information was the most serious problem [ 39 , 40 ]. Nevertheless, communication education provided by most nursing colleges is limited to communication between patients and nurses [ 41 ], and there is also no systematic education on reporting or handing over duties [ 42 ]. Therefore, a program that allows nursing students to experience and practice communication between medical staff in various scenarios is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…This value was higher than the average 3.47 points that was reported by Bae and Park () among fourth‐year nursing students, even though the participants were not in the same grade. Similarly, it was found that the highest score in the expected learning outcomes at the end of the curriculum was in “therapeutic communication and relationships.” These findings mean that nursing is predominantly a relationship‐centered profession and that nursing curriculum tend to focus on improving students' therapeutic communication skills through subjects, such as “nursing communication” (Bae & Park, ; Boschma et al , ; Son, Kim, Koh, & Yu, ).…”
Section: Discussionmentioning
confidence: 99%